Resource misallocation and TFP gap development in Austria - Richard Sellner; Nico Pintar; Norbert Ernst (Oesterreichische Nationalbank (OeNB), 2023)
In this paper we provide firm-level evidence on the role of resource misallocation for total factor productivity development in Austria. We apply the indirect approach of measuring misallocation via the dispersion in marginal products within narrowly defined industries of Hsieh and Klenow (2009) to a firm-level dataset for the period 2008-2018. Our estimates suggest that capital misallocation increased during the recession in the late 2000s, but declined thereafter. This result contrasts with most of the literature on European countries that finds increasing capital misallocation over time, but is compatible with evidence for Austria's main benchmark country and most important trading partner Germany. In line with the literature we find that misallocation is higher in services and for capital. Our estimates suggest that if Austrian efficiency was raised to the US benchmark level, TFP could be raised by 50%. We further find evidence that firms with higher marginal capital/labor productivity build up more capital/labor and that financial constraints play a significant role, especially in the reallocation of capital in Austria.
Keywords: C23; D22; D24; O47; 330; Factor Misallocation; Total Factor Productivity; Austria; Firm Level Data